Efektivitas Pengelolaan Badan Usaha Milik Gampong (BUMG) Gampong Suak Puntong Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Syisyi Haji Rozalia; Fadhil Ilhamsyah (Journal of Social and Policy Issues, 2022)
BUMG is an institution formed by the village in the form of managing various types of businesses whose results can be enjoyed as much as possible for the village community. The purpose of the establishment of BUMG is to obtain a source of original village income with capital from village funds to be managed properly and for the welfare of the village community. This study aims to determine the level of effectiveness of the management of BUMG Suak Puntong and what are the obstacles that affect the management of BUMG Suak Puntong, Kuala Pesisir District, Nagan Raya Regency. This type of research method uses a case study qualitative research. In collecting data, primary and secondary data were used. Based on the results of the study, it was shown that the management of BUMG in Village Suak Puntong, Kuala Pesisir District, Nagan Raya Regency was less effective. The business programs that have been carried out include terracotta rental, chair rental, and savings and loans. Of the three BUMG businesses, only two have been implemented. There are obstacles in the implementation of BUMG, namely from the business managed by the institution, dissatisfaction with the results achieved so far, the BUMG business is still in the development and design stage.